PENGARUH JUS BUAH DURIAN (Durio zibethinus Murr.) TERHADAP PROFIL FARMAKOKINETIK PARASETAMOL PADA TIKUS PUTIH (Rattus norvegicus L.) JANTAN GALUR WISTAR - Pinondang Simaremare; Mohamad Andrie; Bambang Wijianto (Majalah Obat Tradisional, 2013)
Paracetamol is widely used as analgesic and antipyretic agent in treatment of pain and fever. Paracetamol has interaction with carbohydrates and alcohol. Durian is the fruit native of Indonesia, that contain carbohydrates and alcohol. The aims of this research were to study the influence of durian fruit juice to the absorption and elimination kinetics of paracetamol and to know the dose of durian fruit juice that influence the absorption and elimination kinetics of paracetamol. The study was conducted using 16 rats, divided into 4 groups (n=4 per group). Each group was treated the following treatment : control paracetamol (paracetamol 9 mg/200 gBW), dose 1 group (paracetamol 9 mg/200 gBW and 0.675 g/200 gBW of durian fruit juice), dose 2 group (paracetamol 9 mg/200 gBW and 1.350 g/200 gBW of durian fruit juice) and dose 3 group (paracetamol 9 mg/200 gBW and 2.700 g/200 gBW of durian fruit juice). Blood sampling is done from the vein of rat’s tail at minutes 10, 20, 30, 40, 60, 90, 120, 180, 240, 300 and 360. The quantitation of paracetamol in plasma was determined by UV spectrophotometer at 243 nm. Result showed that durian fruit juice changed the absorption kinetics of paracetamol, durian fruit juice decreased Ka,  Cpmaks  and increased  Tmaks  parameter of paracetamol. Durian fruit juice also changed the elimination kinetics of paracetamol, its decreased Vd, Ke, Cl and increased the value of AUC and T1/2 paracetamol. All doses of durian fruit juice can influence the absorption and elimination kinetics of paracetamol includes Ka, Cpmaks, Tmaks, Vd, Cl, Ke, T1/2 and AUC parameters on wistar male rats (Rattus norvegicus L.).